A review on knowledge management systems quality attributes for big data implementation - A. Jabar, Marzanah; Alnatsha, Abdallah S. M. (Faculty of Computer Science an d Information Technology, Universiti Putra Malaysia, 2014)
Knowledge management (KM) is a one of the major function in organizations since it can create, store, retrieve, and transfer knowledge. Nowadays, knowledge increasingly becomes the major resource. It is one of the main features for organizations to gain competitive advantages. Knowledge quality can enhance KMS quality. However, measuring knowledge quality in KM is challenge since there are no accurate measurement criterions, and it will raise an issued in accepting the quality of knowledge that delivered or gained from KMS in organizations. To enhance the quality of KMS, the dimensions of quality should be identified first and this require more research to better define these dimensions. KM metrics have been developed in the last decade but little work has been done on the quality dimensions of KMS, although there is general agreement that the success of KMS is dependent on its quality, there has not been much work on formally defining a comprehensive set of quality dimensions of a KMS. The big data new trend in research has also prompted knowledge management system to also incorporate the new defined characteristic of big data in defining new quality characteristics of KMS. The expected contribution is the definition of a comprehensive set of quality dimensions of a KMS.